Protracted aortic valve closure during peripheral veno-arterial extracorporeal life support: is intra-aortic balloon pump an effective solution?. (January 2019) - Meani, Paolo; Delnoij, Thijs; Raffa, Giuseppe M.; Morici, Nuccia; Viola, Giovanna; Sacco, Alice; Oliva, Fabrizio; Heuts, Sam; Sels, Jan-Willem; Driessen, Rob; Roekaerts, Paul; Gilbers, Martijn; et al.
Background: Left ventricular (LV) afterload increase with protracted aortic valve (AV) closure may represent a complication of veno-arterial extracorporeal membrane oxygenation (V-A ECMO). The aim of the present study was to assess the effects of an intra-aortic balloon pump (IABP) to overcome such a hemodynamic shortcoming in patients submitted to peripheral V-A ECMO. Methods: Among 184 adult patients who were treated with peripheral V-A ECMO support at Medical University Center Maastricht Hospital between 2007 and 2018, patients submitted to IABP implant for protracted AV closure after V-A ECMO implant were retrospectively identified. All clinical and hemodynamic data, including echocardiographic monitoring, were collected and analyzed. Results: During the study period, 10 subjects (mean age 60 years old, 80% males) underwent IABP implant after peripheral V-A ECMO positioning due to the diagnosis of protracted AV closure and inefficient LV unloading as assessed by echocardiography and an absence of pulsation in the arterial pressure wave. Recovery of blood pressure pulsatility and enhanced LV unloading were observed in 8 patients after IABP placement, with no significant differences in the main hemodynamic parameters, inotropic therapy or in the ECMO flow (p=0.48). The weaning rate in this patient subgroup (mean ECMO duration 8 days), however, was only 10%, with another patient finally transplanted, leading to a 20% survival-to-hospital discharge. Conclusion: IABP placement was an effective solution in order to reverse the protracted AV closure and impaired LV unloading observed during peripheral V-A ECMO support. However, the impact on the weaning rate and survival needs further investigations.